Investigating Iraqi Open Educational College EFL Students' Thinking Styles Based on Sternberg's Theory as a Model - Marwan Ramadhan Abdullah, Assist. Lect. (lark, 2025)
The main purpose of this research was to distinguish the preferred thinking styles by Iraqi Open Educational College EFL students in relation to learning English as a foreign language, and with regard to gender and studying level variables. Three hypotheses posed in light of the objectives.       A sample of 40 individuals, including 21 male and 19 female students from the second and fourth stage, randomly selected to investigate the veracity of these assumptions. The sample tasked with administering a survey that the researcher had created using Sternberg's theory of cognitive styles.       To analyze the data obtained from the developed questionnaire, a statistical test, such as the T-test, used.       The main findings revealed that:1- Iraqi Open Educational College EFL students preferred some thinking   styles such as Oligarchic, Legislative and Global more than other ones such as Internal, Monarchic and Local.2- No statistically significant differences of students' thinking styles preferences between male and female students.3- No statistically significant differences of students' thinking styles preference between the second and fourth level of stage students.
Keywords: Thinking Styles, Teaching Styles, Academic Implementation